Planning and budgeting system with a focus on P&L statement within ABB, s.r.o - Procházka, Luboš (2013)
The final project focuses on the budgeting system with special emphasis on the income statement. The first part of the thesis provides a theoretical background of planning and budgeting processes and their main characteristics. It is particularly budgeting that is elaborated on in greater detail. The end of the theoretical part presents the master budget, the key budget in an organization, and gives special attention to budgeted income statement. In the practical part of the thesis, the theoretical background is employed to analyse, discuss and assess the budget system of a specific company, together with its financial and managerial income statements.